Monetary policy or macroprudential policies: What can tame the cycles? - Uwe Vollmer (Journal of Economic Surveys, 2021)
This survey systematizes the rapidly growing literature on the influence of monetary policy and macroprudential policy on the macroeconomy. It examines the impact of monetary policy on the financial cycle and asks how macroprudential instruments influence the efficiency of monetary policy. The questions of whether monetary policy should take account of the financial cycle and lean against the wind is also addressed. The literature review shows that monetary policy is not neutral for financial stability, but should not take into account the financial cycle because the costs probably outweigh the~benefits.
Keywords: 330; asset bubbles; leaning against the wind; macroprudential policies; risk-taking channel